Book Review: Peacebuilding in the Balkans: The View of the Ground Floor - Sumarlan, Yanuar (Journal of Human Rights and Peace Studies, 2019)
Analyses on how the minorities survive in a peace-rebuilding attempt in a post-conflict society have always been interesting. Through an 8-year participant observation in Bosnia, Asst. Prof. Pickering decided to launch this interesting ethnographic-style inquiry. Following Varshney’s (2002) suggestion to overthrow the old studies that looked into just political institutions and elites, the author begins a study on grassroots perspectives. She finds that the minorities must solve their daily problems through political choices that favor the moderate or are inclusive towards the minorities. This book adds and reminds us that beyond “normal” attention to policies from large bodies and majorities, there is a lived experience of the minorities that can be gathered and documented in meaningful ways.